중국학 데이터 크롤링 전략과 시각화 플랫폼 분석 - 박정원; Park Jeongweon (중국연구, 2020)
There is a lot of information online and a variety of data that many users jointly build. By utilizing these data, the scope of research and education can be extended in a way that researchers or educators have not been able to reach. First, from the point of view of Chinese studies, the subject-centered study of analyzing and interpreting text from the researcher's point of view to develop one's own logic is also significant, but it is also a significant study to analyze and interpret the meaning of data existing online (web, app) in the era of Connect. In particular, if the vast amount of data accumulated online in real time is collected in web crawling techniques and expressed in a data visualization tool to the extent that it is not illegal, it will be possible to analyze situations or trends that have not been analyzed before. Second, from the perspective of Chinese studies education, the strength is that data can be compared, intuitively recognized, and shown in three dimensions by collecting various data that exist on paper or the web in a flat and analytical manner, and expressing it in a graph, map, etc. Web publishing of these data visualizations will also maximize their effectiveness. Collect live data in real time and combine it with data visualization tools to maximize expressiveness and provide services to reactive, open Web archive so that everyone can easily access live data. The vast amount of data can enhance the precision of the data, and simply collect, refine and visualize the data using crawling techniques will enhance the competitiveness of research and education. Through this study, the general researchers hope to perform data crawling and visualization as a basis for application to the study.